Human Capital In BPRS For Organizational Efficiency And Employee Productivity - Muhammad Syahrul Hidayat; Nurul Mazidah; Didik Supardana Setia Aksana; Nurhayati (Universitas Darussalam Gontor, 2024)
This study aims to examine and analyze the role of human capital in improving organizational efficiency and employee productivity in Islamic People's Economic Banks (BPRS) in Indonesia. This research was conducted on 350 BPRS employees in East Java Province using purposive sampling technique. While data collection was done through questionnaires. The research was conducted because in 2024 out of 174 BPRS in Indonesia, only 7 BPRS have core capital exceeding Rp 50 billion. This limitation hampers the ability to provide adequate supporting infrastructure and high-quality human resources, especially in a market segment that demands the presence of high-quality human capital. Meanwhile, BPRS are still perceived as inferior to general banks by the public. Thus, this study provides strategic recommendations for BPRS management in improving organizational efficiency and employee productivity through human capital development. The results showed that human capital (HC) has a significant positive influence on improving employee roductivity (EP) with a coefficient value of β = 0.406 (p < 0.05) and organization efficiency (OE) with a coefficient value of β = 0.416 (p < 0.05). In addition, a healthy organization also has a significant positive effect on improving employee productivity (EP) with a coefficient value of β = 0.262 (p < 0.05). Overall, a healthy organization mediates the relationship between human capital and employee performance with an axb indirect effect value of 0.109 (p < 0.05).